Sexual dysfunction among males and females with bipolar disorder and healthy subjects: The burden of illness severity - Dargél, Aroldo A.; Mosconi, Elise; Volant, Stevenn; Taieb, David; Brenot, Philippe (Bipolar disorders, 2022)
Objectives Sexual dysfunction has wide‐ranging impacts on the person's functioning and quality of life, being associated with higher severity of psychiatric illnesses and poor therapeutic response. Given the paucity of data on this topic in bipolar disorder (BD), we investigated sexual functioning among males and females with BD and healthy controls (HCs) as well as whether illness severity markers and subthreshold mood symptoms were associated with sexual dysfunctions in BD patients. Methods The study included 80 BD outpatients and 70 HCs. Sexual functioning was evaluated using the validated, gender‐specific Changes in Sexual Functioning Questionnaire (CSFQ‐14). Results BD patients had a significantly poorer sexual functioning than HCs (p < 0.00001). The odds of sexual dysfunction doubled given a one‐unit increase in the number of suicide attempts (adjusted OR = 2.01, 95% CI:1.23–3.55; p < 0.01) and increased by 60% for every additional hospitalization (p < 0.05). Greater illness duration was associated with arousal/orgasmic (p < 0.05) and overall sexual dysfunctions (p < 0.01). BD patients with more mixed or (hypo)manic episodes had a lower likelihood of libido loss and arousal/orgasmic disturbances (p < 0.01), respectively. Higher levels of subthreshold depressive symptoms increased by 20% the odds of sexual interest/frequency dysfunctions (p < 0.05), and up to 60% regarding orgasmic disturbances (p < 0.01). Conclusions Sexual functioning may be a useful proxy of illness severity as well as a relevant dimension to more deeply characterize BD patients. Further studies are warranted to replicate our findings, to evaluate temporal associations between sexual dysfunctions and illness severity across the BD mood and treatment spectrums and to explore neurobiological underpinnings of these associations.